A Preliminary Study of the Gold Content of Byzantine Coins and a Possible Link to the Supernova of Year AD 1054 - Kasper Mayntz Paasch (Heritage, 2025)
A series of 11 Byzantine gold coins were investigated, including two examples of an extremely rare type called histamenon “stellatus”, from around the reign of the Byzantine emperor Constantine IX Monomachos (AD 1042–1055). The methods applied were X-ray fluorescence spectroscopy (XRF), specific density measurement (SD), and scanning electron microscopy (SEM). The debasement (decreasing gold content) of the Byzantine nomisma gold coinage during the 11th century was demonstrated. A method combining XRF and SD measurement combined with a graphical presentation/analysis called a ternary plot was also demonstrated. The measured gold content of the 11 coins was corrected for the possible “outwashing” effect and a potential cleaning of ancient gold. A model for the estimation of the gold content of Byzantine histamenon nomisma gold coins from the period AD 1020–1118, based on the specific density (SD), was derived. It was demonstrated that two analyzed histamenon “stellati” coins likely were minted around AD 1054–1055, possibly during the same period as the occurrence of the supernova SN1054, known as the Crab-nebula. It is further discussed if the gold content and size of the stars shown on those coins can be correlated to the visibility of the supernova from June AD 1054 to January AD 1055.